Techniques and Results for Open Hip Preservation - Levy, David M.; Hellman, Michael D.; Haughom, Bryan; Stover, Michael D.; Nho, Shane J. (Frontiers in Surgery, 2016)
While hip arthroscopy grows in popularity, there are still many circumstances under which open hip preservation is most appropriately indicated. This article specifically reviews open hip preservation procedures for a variety of hip conditions. Femoral acetabular impingement may be corrected using an open surgical hip dislocation. Acetabular dysplasia may be corrected using a periacetabular osteotomy. Acetabular protrusio may require surgical hip dislocation with rim trimming and a possible valgus intertrochanteric osteotomy. Legg-Calve ́-Perthes disease produces complex deformities that may be better served with osteotomies of the proximal femur and/ or acetabulum. Chronic slipped capital femoral epiphysis (SCFE) may also benefit from a surgical hip dislocation and/or proximal femoral osteotomy.